Diagnosis and management of acute lower gastrointestinal bleeding: guidelines from the British Society of Gastroenterology. Issue 5 (12th February 2019) - Oakland, Kathryn; Chadwick, Georgina; East, James E; Guy, Richard; Humphries, Adam; Jairath, Vipul; McPherson, Simon; Metzner, Magdalena; Morris, A John; Murphy, Mike F; Tham, Tony; Uberoi, Raman; et al.
Abstract : This is the first UK national guideline to concentrate on acute lower gastrointestinal bleeding (LGIB) and has been commissioned by the Clinical Services and Standards Committee of the British Society of Gastroenterology (BSG). The Guidelines Development Group consisted of representatives from the BSG Endoscopy Committee, the Association of Coloproctology of Great Britain and Ireland, the British Society of Interventional Radiology, the Royal College of Radiologists, NHS Blood and Transplant and a patient representative. A systematic search of the literature was undertaken and the quality of evidence and grading of recommendations appraised according to the GRADE(Grading of Recommendations Assessment, Development and Evaluation) methodology. These guidelines focus on the diagnosis and management of acute LGIB in adults, including methods of risk assessment and interventions to diagnose and treat bleeding (colonoscopy, computed tomography, mesenteric angiography, endoscopic therapy, embolisation and surgery). Recommendations are included on the management of patients who develop LGIB while receiving anticoagulants (including direct oral anticoagulants) or antiplatelet drugs. The appropriate use of blood transfusion is also discussed, including haemoglobin triggers and targets.